2017
DOI: 10.1109/tuffc.2017.2654125
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Utility of the Parabolic Approximation in Medical Ultrasound Using Wide-Angle Diffraction Modeling

Abstract: Wide-angle parabolic models are commonly used in geophysics and underwater acoustics but have seen little application in medical ultrasound. Here a wide-angle model for continuous-wave high-intensity ultrasound beams is derived which approximates the diffraction process more accurately than the commonly-used Khokhlov-Zabolotskaya-Kuznetsov (KZK) equation without increasing implementation complexity or computing time. A method for preventing the high spatial frequencies often present in source boundary conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Nevertheless, Table I shows that (12) predicts FWHM consistent with values obtained by simulation [87] and experiment [14]. For smaller f-numbers, alternative diffraction models may be required [85, 86].…”
Section: Theorysupporting
confidence: 64%
See 2 more Smart Citations
“…Nevertheless, Table I shows that (12) predicts FWHM consistent with values obtained by simulation [87] and experiment [14]. For smaller f-numbers, alternative diffraction models may be required [85, 86].…”
Section: Theorysupporting
confidence: 64%
“…HIFU Simulator solves the KZK equation, which is the quadratic approximation of the Westervelt equation (not to be confused with the quadratic spatial averaging model discussed previously). The KZK equation is theoretically valid up to angles of about 15-20° from the propagation axis (roughly equivalent to F# > 1.5) [86, 92]. However, it has been reported that the KZK equation can be relatively accurate in the frequency domain about 25° from the transducer axis (F# = 1) [92].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other computational tools to assess specific aspects of device performance or safety that industry can employ include a simulator for high-intensity focused ultrasound (HIFU) beams and heating effects ( 50 , 51 ), benchmarks models for computational fluid dynamics ( 19 ), patient-specific workflows for assessing clot trapping efficiency in IVC filters ( 52 ), surrogate models for predicting device-specific and species-specific hemolysis (Craven et al, under review), optical-thermal light-tissue interactions for photoacoustic breast imaging ( 53 ), and an online app for assessing the safety of color additives ( 54 ).…”
Section: Computational Modeling Researchmentioning
confidence: 99%
“…Hydrophones can distort pressure signals due to 1) frequency-dependent sensitivity and 2) spatial averaging across the finite sensitive element. These forms of distortion are relevant to HITU signals, which can be highly nonlinear and can therefore have very broad bandwidths due to the presence of multiple harmonics [28,29,[40][41][42][43]. Nonlinearity affects spatial averaging because as harmonic frequency increases, harmonic beam width decreases [40,[44][45][46][47][48][49] and the potential for harmonic spatial averaging increases [50,51].…”
Section: Introductionmentioning
confidence: 99%